Economic Growth Modelling in West Nusa Tenggara Using Bayesian Spatial Model Approach - Soraya, Siti; Herawati, Baiq Candra; Negara, Habib Ratu Perwira (Universitas Muhammadiyah Mataram, 2021)
Economic growth is a measure of the welfare of the people in an area. Economic movement is characterized by the number of goods and services produced. The high amount of goods produced and the services used are of course strongly influenced by the amount of available capital, the labor involved, and the level of technology used. The measuring instrument or a reflection of economic growth is the Gross Regional Domestic Product (GRDP). The purpose of this study is to model economic growth in NTB in 2018. In this study, GRDP modeling was carried out using the Bayesian Spatial approach. Based on the results of testing the spatial dependency and spatial heterogeneity, it shows that there is a spatial dependence on the GRDP of districts / cities in NTB Province.. From the analysis conducted, it was found that was positive and insignificant at the 10% level. The parameter estimation results show that the number of workers, the value of capital and the number of workers weighed are variables that have a significant effect on the model. Thus the GRDP of an area in West Nusa Tenggara is influenced by the number of workers, the value of capital and the total labor weight and the GRDP of other surrounding areas.